An Analysis of Selectivity Bias in the Medicare AAPCC - Dowd, Bryan (CENTERS for MEDICARE & MEDICAID SERVICES, 1996)
Using econometric models of endogenous sample selection, we examine possible payment bias to Medicare Tax Equity and Fiscal Responsibility Act of 1982 (TEFRA)-risk health maintenance organizations (HMOs) in the Twin Cities in 1988. We do not find statistically significant evidence of favorable HMO selection. In fact, the sign of the selection term indicates adverse selection into HMOs. This finding is interesting, in view of the fact that three of the five risk HMOs in the study have since converted to non-risk contracts.